(untitled) (American Journal of Islam and Society, 2005)
During the events that led to the “soft coup” of the Erbakan-Çiller coalition government in 1997, the Turkish military declared that the number one threat to national security was not Kurdish separatism, but Islamic radicalism. Despite this shift in security strategy, the Justice and Development party, which was born from the ashes of Erbakan’s openly Islamist Refah party, won a decisive victory at the polls in November 2002. These series of events from Turkey’s recent history have raised many questions in the minds of observers, both international and domestic, as to the nature and strength of Islamic political and social movements in the Republic of Turkey – a state that since its birth in 1923 had undergone a systematic program of westernization and secularization. In his Islamic Political Identity in Turkey, M. Hakan Yavuz attempts to answer these very questions by providing a comprehensive analysis of the main Muslim social groups that have come to dominate Turkish-Muslim society, namely, the Nakshibendi Sufi orders and the Nurcu movement. These groups have made significant inroads into Turkish civil society, crossing class, regional, and ethnic lines, by taking advantage of new opportunity spaces in the market, the print media, and education. This was a direct result of the political and economic liberalization policies of the Özal government during the 1980s. As the author argues, “the secularizing, state-centric elite failed effectively to penetrate and transform traditional society, and was similarly unsuccessful in developing an alternative value system and associational life for the rural population of society” (p. 4). Thus, the social and ethical vacuum created by the Kemalists was appropriated by a diverse group of Islamic social movements that were then urbanized by way of the gecekondus, the shanty-towns built overnight by rural migrants to the big cities during the 1960s and 1970s. These movements, which were silently germinating in the Anatolian countryside, underwent what Yavuz aptly terms the “vernacularization ...